Enhancing the Orthognathic Surgery Experience: Treatment in 10 Weeks “Surgery First” Approach - Salazar, Aylin Gallegos (Ann Maxillofac Surg, 2020)
This case report describes the successful treatment of a 25-year-old male with maxillary retrognathism, skeletal and dental Class III malocclusion, anterior and posterior crossbite, negative overjet and overbite, mild mandibular crowding, and lower midline deviation. The nonextraction treatment plan included: (1) maxillary and mandibular arch fixed appliance and (2) Le Fort 1 maxillary osteotomy and postsurgical orthodontic treatment. The orthodontic treatment was initiated with 0.022” preadjusted brackets bonded to all the teeth except the maxillary second molars, 2 days before the surgery without any archwires. Two weeks after the surgery, maxillary and mandibular arch alignment along with the occlusal adjustments was started with the use of 0.018” NiTi wires, in both arches. Optimum esthetic and functional results were achieved in 10 weeks after the surgery, with the cooperation of two specialties and the use of surgery first approach.